E-Textiles 2022: The 4th International Conference on the Challenges, Opportunities, Innovations and Applications in Electronic Textiles - Beeby, Steve; Yang, Kai; Torah, Russel; Hughes-Riley, Theodore (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Proceedings reprint is a collection of papers from the E-Textiles 2022 Conference and represents the state of the art from both academia and industry in the development of smart fabrics that incorporate electronic and sensing functionality. The Proceedings reprint presents a wide range of applications of the technology, including wearable textile devices for healthcare applications such as ECG measurements and functional electrical stimulation. Manufacturing approaches include printed smart materials, knitted e-textiles and flexible electronic circuit assembly within fabrics and garments. Supplying power is a constant challenge for all wireless wearable technologies, and therefore this collection includes papers on triboelectric energy harvesting and zinc-ion batteries fabricated on top of textile substrates.